A longitudinal study of quality of life and functional status in total hip and total knee replacement patients. Issue 2 (May 2015) - Mandzuk, Lynda L.; McMillan, Diana E.; Bohm, Eric R.
Abstract Background Primary total hip and primary total knee surgeries are commonly performed to improve patients' quality of life and functional status. Aim This longitudinal retrospective study (N = 851) examined self-reported quality of life and functional status over the preoperative and postoperative periods: 12 months prior to surgery, one month prior to surgery and 12 months following surgery. Methods A linear mixed effects model was used to analyze the changes in quality of life and functional status over the sampling period. Results Patients in the convenience sample reported improvements in quality of life and functional status utilizing the SF-12 and Oxford Hip and Oxford Knee, although differences were noted by procedure and gender. Total hip patients tended to demonstrate greater improvement than total knee patients and males reported higher levels of physical and mental quality of life as well as functional status when compared to females. Of particular note was that mental health scores were consistently lower in both total hip and total knee replacement patients across the perioperative period and up to one year postoperative. Conclusion This study identifies an opportunity for health care providers to proactively address the mental health of total hip and total knee replacement patients throughout their joint replacement trajectory.